Heart size and function in acromegaly. Issue 6 (June 1979) - Mather, H M; Boyd, M J; Jenkins, J S
Abstract : Cardiac size and function was studied in 23 acromegalic patients using echocardiography and systolic time interval measurements. Thirteen patients (56%) had increased left ventricular mass, and in the 20 treated patients this correlated well with the mean of the recent basal growth hormone levels. It is suggested that myocardial hypertrophy may regress in proportion to the degree of control of growth hormone levels. The ejection fraction was normal in all patients except one, and increased left ventricular mass was not associated with detectable impairment of left ventricular performance. Thus, most acromegalic hearts function normally even when their mass is considerably increased, though the long-term effects of this are unknown, Echocardiography will be valuable in the serial monitoring of the cardiac effects of acromegaly.